UTILIZATION OF MACHINE TECHNOLOGY IN INCREASING INSTANT GRINGER PRODUCTION - Asnawi; Ronald Fransyaigu; Hanafiah; Ary Kiswanto Kenedi; Suheri (LPPM dan PM Universitas Samudra, 2021)
The ginger industry in East Aceh district is widely developed through home industries which are an important part of small and medium industries. This industry is mostly done by housewives on the sidelines of their busy household. The